2021
DOI: 10.1093/eurheartj/ehab724.2670
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular evaluation with exercise testing using face mask during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic is associated with more than 127 million of infected people and 2.7 million deaths in the world. However, cardiovascular diseases are still a worldwide main health problem. Patients are afraid to go to the hospital because of the risk of being infected with SARS-COV2. In particular, exercise testing (ET) has been underused, due to the fear of the airborne aerosol generation. There are cardiology centers performing ET that ask patient to wear a mask, although i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In this review, one particular study demonstrated that at rest, a mild increase in heart rate by 5.6% was noted whilst wearing an N95 respirator in comparison to not wearing a mask [ 8 ]. These findings were replicated in other studies such as by Ilarraza-Lomelí et al [ 12 ]. However, both authors commented that the results were not statistically significant to draw the conclusion that the elevated heart rate was an effect of the N95 mask.…”
Section: Reviewsupporting
confidence: 83%
See 2 more Smart Citations
“…In this review, one particular study demonstrated that at rest, a mild increase in heart rate by 5.6% was noted whilst wearing an N95 respirator in comparison to not wearing a mask [ 8 ]. These findings were replicated in other studies such as by Ilarraza-Lomelí et al [ 12 ]. However, both authors commented that the results were not statistically significant to draw the conclusion that the elevated heart rate was an effect of the N95 mask.…”
Section: Reviewsupporting
confidence: 83%
“…One of these studies compared exercise tests performed prior to the pandemic without any mask against those performed during the pandemic whilst using an N95 mask [12]. A key finding from this cross-sectional study was that there was an increase in the number of exercise tests that were suspended due to dyspnoea compared to those tests conducted during the pandemic with an N95 mask [12]. This is a very relevant finding since it illustrates that N95 respirators can potentially lead to greater levels of shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation